MODERASI ISLAM PENCANTUMAN PENGHAYAT KEPERCAYAAN DI KOLOM KTP/KK DALAM NALAR MAQASID - Hamka Husein Hasibuan (IAIN Manado, 2019)
Abstract This article analyzes the decision of the Constitutional Court (MK) which rules that Penghayat Kepercayaan (the indigenous believers) has the right to include their credentials on their Identity (KTP) and Family Cards (KK). Using the “maqasid” approach, this article provides alternative answers, mediating the accepting and rejecting parties. The moderation of Islam is concluded, when the maqasid is used as reasoning sources in seeing things which bridges between texts and the reality besides considering the reasonality. By using the Jasser Auda’s maqasid paradigm, the paper concludes that inclusion of the local faith as their religious identity on the state documents is a part of development and human rights in the nation-state framing. Keywords: Identity, indigenous believer, Maqasid, MK, and Human Right.Abstrak Artikel ini menganalisis Putusan Mahkamah Konstitusi tentang Pencantuman Penghayat Kepercayaan di kolom KTP/KK dengan menggunakan konsep maqasid. Dengan pendekatan maqasid, artikel ini memberikan jawaban alternatif, sebagai sintesis antara pihak yang menerima dan pihak yang menolak. Moderasi Islam itu tampak, ketika maqasid digunakan sebagai nalar dalam melihat sesuatu, yang bisa mendialogkan antara teks dengan realitas yang berkembanga dengan tetap berpegang kepada kekuatan nalar. Dengan menggunakan paradigma maqasid Jasser Auda, maka pencantuman itu merupakan bagian dari development (pembangunan) dan human right (hak insani). Kedua poin ini diletakkan dalam kerangka nation-state.Keyword: Identitas, Penghayat, Maqasid, MK, dan Human Right.